Autonomy, Dignity and Happiness: Towards a Project for the Self-Realization of People with Intellectual Disabilities (Revista Iberoamericana de Bioética, 2021)
Though people with intellectual disabilities have certain limitations, they possess other capacities that give them a certain degree of autonomy in their daily lives. What they require is sufficient legal coverage and support to facilitate their personal growth and complete social integration. Suitable companionship depending on their cognitive level, provided by professionals, their families, and society, is essential if they are to lead fulfilling lives. Happiness and disability are not mutually exclusive concepts if a person feels sufficiently valued and supported.
Keywords: dignity; autonomy; intellectual disability; support; happiness